IMPROVING STUDENTS’ READING COMPREHENSION BY USING NHT TECHNIQUE ATTHE TWELFTH GRADE STUDENTS OF MAN 3 SOLOK IN ACADEMIC YEAR 2022/2023 - Wita Purnama Sari; Reflinda Reflinda; Melyann Melani; Irwandi Irwandi (International Journal of Teaching and Learning, 2025)
This research aimed to find out whether there was an improvement in students’ reading comprehension by using the NHT technique among the twelfth-grade students of MAN 3 Solok. This research was a Classroom Action Research (CAR). The research data were collected through observation and tests. The test is given to the students in the form of a reading comprehension post-test at the end of learning at each cycle. The subject of this research was the twelfth grade of religion students of MAN 3 Solok. The total number of students in the class was 28 students. The result of the analysis showed that the NHT technique could improve students’ reading comprehension. It was shown from the result of students’ reading comprehension test in two cycles. The result of the reading comprehension test showed that there were improvements in students’ reading comprehension scores by using the NHT technique. On the initial score of students (pretest), the average score of the class was 56,08. The result obtained by students in the cycle I (post-test) the average score of the class was 72,59. In the cycle II results obtained by students, the average score of the class was 79.10. Based on the students’ results in cycle I and cycle II can be concluded that the minimum criteria of score was reached. The minimum criteria for the score (KKM) was 75. Furthermore, it can be concluded that the use of the NHT technique could improve students’ reading comprehension.